2017
DOI: 10.1097/ico.0000000000001173
|View full text |Cite
|
Sign up to set email alerts
|

Application of Scanning Electron Microscopy With Energy-Dispersive X-Ray Spectroscopy for Analyzing Ocular Surface Particles on Schirmer Strips

Abstract: Purpose To demonstrate the application of Scanning Electron Microscopy with Energy-Dispersive X-Ray Spectroscopy (SEM/EDS) for analyzing Schirmer strips for particle concentration, size, morphology, and type distribution. Methods A cross-sectional design was used. Patients were prospectively recruited from the Miami Veterans Affairs (VA) Healthcare System eye clinic and underwent a complete ocular surface examination. Size, type and chemical composition of PM Schirmer strips (from the left eye) were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…The present SEM–EDX analysis proposes that the biological plausibility of the element's analysis of the pecten oculi may be affected by the overdose of these elements, as it may lead to oxidative stress and physical eccentricity. With the inflammation state, similar findings were described by (Avula et al, 2017; Elghoul et al, 2021). Recently, we were required to understand the important roles of this element's analysis of the pecten oculi and describe their intense relationship with the visually active hours and the retina characterizations to know the visual strength of the different avian species in the various feeding styles.…”
Section: Discussionsupporting
confidence: 88%
“…The present SEM–EDX analysis proposes that the biological plausibility of the element's analysis of the pecten oculi may be affected by the overdose of these elements, as it may lead to oxidative stress and physical eccentricity. With the inflammation state, similar findings were described by (Avula et al, 2017; Elghoul et al, 2021). Recently, we were required to understand the important roles of this element's analysis of the pecten oculi and describe their intense relationship with the visually active hours and the retina characterizations to know the visual strength of the different avian species in the various feeding styles.…”
Section: Discussionsupporting
confidence: 88%
“…Our SEM–EDX findings suggested that the composition of the different elements of the pecten oculi may refer to the surrounding environmental conditions and the extent to which it contains airborne pollutants. Our SEM–EDX findings suggested that the biologic plausibility of the presence of these elements on the pecten oculi surface can influence the pecten oculi surface health as the overdose of these elements on the pecten oculi surface may lead to oxidative stress and physical abrasions, with inflammatory effects, similar to that reported by Avula et al (2017) and Wolkoff (2010). Future studies will be needed to complete this work, by comparison, the SEM–EDX findings of the pecten oculi with the retina to know more about the vision ability of the different or the same avian species in the different or the same environmental conditions.…”
Section: Discussionsupporting
confidence: 86%
“…With the exception of a few hazardous substances, data on the skin and systemic toxicity of most air pollutants are limited. The first step in understanding the potential health risks associated JEADV 2022, 36, 1376-1381 Table 1 Classification of particle groups based on their morphology and elemental composition [6][7][8] No Use of SEM/EDX methods for the analysis of ambient particulate matter adhering to the skin surface with skin exposure to AP is to identify relevant chemicals and quantitatively assess the exposure. 2 SEM-ED2X may provide new insights into the link between exposure to AP and APinduced skin damage.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature review on elemental composition, 6,9–13 clustering rules and morphology, the particles were classified into major groups and subgroups that further defined their elemental composition, size, morphology and possible sources. Biogenic and unclassified particles were counted, with no additional chemical or geometrical specification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation